Screening of Mycotoxins Producer Fungal and Aflatoxins Level in Dried and Smoked Fish (Clarias Sp.) and (Oreochromis Sp.) from Lake Fitri - Chad - Ousman, Abdoullahi Hissein; Flibert, Guira; Tidjani, Abdelsalam; Fulbert, Nikiéma; Elie, Kabré; Raoul, Bazié Bazoin Sylvain; Lawane, Abakar Idriss; Aly, Savadogo (Journal of Food Technology Research, 2019)
Fish is a protein source of high nourishing value consumed in the entire world. In Saharan countries it is consumed fresh, however as dried or smoked. However, fish is subject to both fungal and mycotoxins contamination. This study aims to identify fungal presumed producing mycotoxin and to evaluate the contamination level of aflatoxins B1, B2, and G2. A total of 150 samples of dried and smoked fish (Clarias sp. and Oreochromis sp.) have been collected in different islands of the Fitri lake. Standard methods of microbiology have been used for fungal isolation and identification. Aflatoxins content in fish has been determined using HPLC associate to GCMS. Fifty samples (50) were contaminated by four major fungal kinds. Frequency of fungal was to 40 % (Aspergillus niger), 26 % (Aspergillus fumigatus), 20 % (Mucor sp), 8% (Curvularia spp) and 6% (Scycadium). Twenty (20) samples suspected to be contaminated and analyzed, only seven (7) was contaminated with aflatoxins (B1, B2 and G2). The aflatoxin contamination level vary according to the fish species. Clarias sp. samples are 50 % contaminated by aflatoxins when Oreochromis sp are 20 % contaminated. Aflatoxins rates ranged from 0.01 to 2.78 and 0.09 to 0.32 µg/Kg respectively for aflatoxin B1 and aflatoxin B2 for Clarias sp and from 0 to 0.4 µg/Kg of aflatoxin B2 for Oreochromis sp. The mycotoxins level is in average high than the European Union recommendation for dried product. These results call for more sensitization and training for producer for safe dried and smoked fish.